CART - an Arabic teaching-learning tool for non-native Arabic speakers - Shuib, Ahmad Hasanul Ishraf; Abdul Aziz, Normaziah; Mat Daud, Nuraihan; Hasan, Haslin (IEEE, 2014)
Teaching and learning Arabic language is not an easy task for non-native Arabic speakers. Computer Aided for Language Learning (CALL) has been used by many learning institutions to address this issue. Various teaching-learning techniques and features can be embedded in CALL to compliment the conventional method of language teaching and learning. This paper will describe two useful components i.e.